Outcome Of Inguinal Hernia Surgery Done Laparoscopically- Retrospective Analysis Of 15 Years (Journal of Pharmaceutical Negative Results, 2022)
Background and Objective- Laparoscopic hernia repairs are used increasingly in adults. The purpose of this study was to analyze the outcome of adults treated surgically for unilateral or bilateral inguinal hernia using laparoscopy.Methods- We conducted a retrospective, single-center outcome analysis of laparoscopic inguinal hernia repair in adults (18-90 years) that complied with STROBE standards. Our research received the local Ethics Committee. This study comprised 1500 adults who underwent consecutive laparoscopic surgery between March 2, 2017, and March 1, 2022. The prospective questionnaire (issued by mail or filled out during a structured telephone interview) and the hospital records served as the basis for data analysis. The median follow-up period between the operation and when families responded to the questionnaire was 60 months (range: 13–68 months). To verify that the internal ring was properly closed, the knot was knotted intra- or extracorporally and examined. In our study, two distinct surgical methods were study. We used the intraperitoneal, intracorporal knot method in 750 (50%) 1500 of patients. Surgeons used the extracorporal/extraperitoneal knot method on remaining 750 patients. SPSS was used for analysis.Results- the mean age in IKM was 43.4 years and 44.1 years in EKM which was not significant. The study was male preponderance comprising 60% of patient load. The most common location of hernia was unilateral in 40% of cases followed by bilateral. Recurrence rate was higher in EKM and was significant. Postoperative problems were observed in (1.6%) patients who are higher in EKM but not significant. These were postanesthetic problems such as sore throat and cough. Post-operative infections (granuloma or abscess at the umbilical incision site) during the first month after surgery were observed in (1.6%) patients. Disturbing postoperative pain was reported by 42 (5.6%) patients through intraperitoneal knot method and (8.6%) through extraperitoneal knot method. So post operative pain was higher in EKM and it was significant.Conclusion- Laparoscopic inguinal hernia repair carries a learning curve and is safe and efficient in adults thereafter. Further prospective studies are required to evaluate the long-term outcome of laparoscopic inguinal hernia repair in adults.